30 Predicting gestational age improves newborn screening for congenital adrenal hyperplasia. (19th August 2020) - Jomaa, Danny; Henderson, Matthew; Hawken, Steven; Chakraborty, Pranesh
Abstract: Background: Newborn screening for congenital adrenal hyperplasia is performed using a two-tier approach. The first tier involves comparison of neonate 17-hydroxyprogesterone levels to gestational age (GA)-based thresholds. When GA is unreported, which occurs in approximately 5% of births, birth weight (BW)-based thresholds are the only available option. However, these have a lower specificity and result in more false positive results. Recently, a predictive model was developed to estimate GA based on newborn demographics and the screening analytes measured in a blood sample. Objectives: The objective of this study was to determine whether supplying a predicted GA to newborns with unreported GA, and subsequent GA-based screening, has a higher positive predictive value than BW-based screening. Design/Methods: Screening data was obtained for approximately 700, 000 births that occurred in Canada between 2011 and 2015. Predicted GA was calculated using a model composed of demographic and screening analyte factors. The positive predictive values of BW- and predicted GA-based screening were calculated for newborns with unreported GA. A sequential approach was then developed whereby newborns with unreported GA were first screened by BW-based screening. Newborns that screened positive were then supplied with their predicted GA and screened using GA-based thresholds. Results: First-tier CAH screening using GA-based 17-hydroxyprogesterone thresholds had a higher positive predictive value than using BW-based thresholds (1.30% vs. 0.82%). In the study time period, 3.61% of newborns had an unreported GA. For these newborns, predicted GA-based screening had a higher positive predictive value than BW-based screening (0.83% vs. 0.76%) and correctly identified the 2 infants with CAH whose GA was unreported. A sequential screening approach was then used: BW-based screening and, for the screen positive population, predicted GA-based screening. This further increased the positive predictive value compared to BW-based screening (0.95% vs. 0.76%), reduced the false positive rate, and correctly identified true positive cases. Conclusion: Reducing the false positive rate of CAH screening is important to prevent unnecessary second-tier screening and referrals. For newborns with unreported GA (4-5% of all births), BW-based screening is the only currently available approach. However, this approach has a poor specificity and a high false positive rate compared to GA-based screening. This study is the first to demonstrate an alternative screening strategy with a higher positive predictive value for newborns with unreported GA.